Examination of the effectiveness of FF MARS in a CATR through electromagnetic simulation. Issue 4 (21st February 2018) - Gregson, Stuart Fraser; Parini, Clive G.; Newell, Allen C.
Abstract : For more than a decade now, a measurement and post‐processing technique involving modal filtering, named mathematical absorber reflection suppression (MARS), has been used very successfully to identify and subsequently extract range reflections in spherical, cylindrical and planar near‐field antenna test systems and far‐field (FF) and compact antenna test ranges (CATRs). Much of the early work concentrated on verification through experimental testing; however, some additional validation was performed using computational electromagnetic (EM) simulations. These considered first FF and subsequently near‐field cases. The recent development of an accurate, flexible EM simulation tool that enables the simulation of 'measured' FF pattern data as obtained from using a CATR has, for the first time, permitted the careful verification of the FF‐MARS technique for a specified antenna under test (AUT) and CATR combination. This study presents simulated 'measured' FF antenna pattern data in the presence of a large scatterer and then verifies the successful extraction of the scattering artefacts. In addition to considering range reflections, feed spill‐over is also treated. Results are presented and discussed.